Beragam Seni Pertujukkan di Era Jawa Kuno - Sadono, Soni; Pandanwangi, Brilindra; Kasputra, Danil (Perkumpulan Program Studi Sejarah Se-Indonesia, 2025)
This study reviews various forms of performing arts that developed in Java during the classical period or the Hindu-Buddhist period. This study uses historical methods through the stages of heuristics, criticism, interpretation, and historiography to explore and reveal the various performing arts that existed in the Ancient Javanese era. One of the most striking forms of performing arts is Wayang Art, which is divided into Wayang Beber and Wayang Purwa. Wayang Beber is a performance that depicts an epic story by spinning rolls of cloth filled with images, while Wayang Purwa is a performance of wooden or leather puppets that reflect mythological and epic stories. Dance is also an integral part of Ancient Javanese performing culture, with various types of dances reflecting the beauty of movement and expression of Javanese culture. Musical arts, including instruments such as gamelan and other traditional musical instruments, play an important role in accompanying dance and puppet performances. In addition, the art of comedy (classical Javanese) is also an inseparable part of the Ancient Javanese performing arts. This is a form of entertainment that combines comedy, social criticism, and moral messages. Through these various forms of performing arts, Ancient Javanese culture expresses its intellectual wealth and artistic expression, which remain a valuable heritage in Javanese culture to this day. This performing art is not only entertaining but also teaches deep values ​​and history to the next generation, making it an irreplaceable part of Javanese cultural identity.